The role of hydrogen in hardening/softening steel: Influence of the charging process. (October 2015) - Zhao, Yakai; Seok, Moo-Young; Choi, In-Chul; Lee, Yun-Hee; Park, Seong-Jun; Ramamurty, Upadrasta; Suh, Jin-Yoo; Jang, Jae-il
Graphical abstract: Abstract : Thermal desorption spectroscopy and nanoindentation techniques were employed to elucidate the key differences in the hydrogen (H) charging methods (electrochemical versus gaseous) and their consequences on the mechanical response of a low carbon steel. While electrochemical charging enhances the hardness, gaseous charging reduces it. This contrasting behavior is rationalized in terms of the dependency of the strength on the absorbed amount of H during charging and the H concentration gradient in the specimen.